2008
DOI: 10.1164/rccm.200709-1400oc
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Improves Survival in Sepsis via Enhanced Hepatic Bacterial Clearance

Abstract: These studies show that the decline in IGF-1 levels in sepsis is related to bacterial clearance and that replacement of IGF-1 in a murine model of sepsis improves overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 58 publications
2
28
0
1
Order By: Relevance
“…Similar to the portal vein bacterial load, there was evidence of enteric bacteria in the liver at baseline, suggesting the GI tract as the source of these bacteria. We have previously demonstrated that IGF-1 levels are reduced during sepsis (16). Figure 2C demonstrates confirmation that serum IGF-1 levels, as measured by ELISA, are reduced in our murine model of Pseudomonas bacteremia and sepsis.…”
Section: Enteric Bacteremia Is Inversely Correlated With Serum Igf-1 supporting
confidence: 84%
See 4 more Smart Citations
“…Similar to the portal vein bacterial load, there was evidence of enteric bacteria in the liver at baseline, suggesting the GI tract as the source of these bacteria. We have previously demonstrated that IGF-1 levels are reduced during sepsis (16). Figure 2C demonstrates confirmation that serum IGF-1 levels, as measured by ELISA, are reduced in our murine model of Pseudomonas bacteremia and sepsis.…”
Section: Enteric Bacteremia Is Inversely Correlated With Serum Igf-1 supporting
confidence: 84%
“…This suggests that decreased IGF-1 levels during sepsis likely contribute to the subsequent development of bacterial translocation. Our previous studies showed that IGF-1 treatment also results in decreased organ injury and improved outcome in murine sepsis (16). As a group, these data suggest that one potential mechanism for improved outcome after IGF-1 therapy is decreased bacterial translocation.…”
Section: Enteric Bacteremia Is Inversely Correlated With Serum Igf-1 mentioning
confidence: 74%
See 3 more Smart Citations